Captain Underpants and the Terrifying Return of Tippy Tinkletrousers : Captain Underpants #9 - Pilkey, Dav, 1966- (New York : Scholastic, 2012)
Having changed the course of human history after unwittingly wondering what could be worse than going to prison, George and Harold are catapulted through time back to their kindergarten days, where they are subjected to a sixth-grade bully and a clueless school principal.
Keywords: Time travel -- Fiction; Schools -- Fiction; School principals -- Fiction; Superheroes -- Fiction; Time travel -- Fiction; School superintendents and principals -- Fiction; Superheroes -- Fiction; School stories; Humorous fiction; Humorous fiction